Turner syndrome in a neonate - Patil, Namrata; Wade, Poonam; Singh, Vinaya; Gandhi, Prachi; Malik, Sushma (International Journal of Contemporary Pediatrics, 2020)
Turner’s syndrome (TS) is the common chromosomal abnormality. However, it is diagnosed rarely in the neonatal period. In many cases the diagnosis of TS may be delayed until childhood, when evaluation for short stature yields the diagnosis, or adolescence, when combination of growth failure and pubertal delay suggests the possibility of TS. Girls with TS are usually treated with growth hormone and oestrogen replacement therapies for short stature and oestrogen deficiency. A multidisciplinary team is usually required for management. Authors report an 11 day old infant who was diagnosed as Turner’s syndrome. The classic clinical feature, lymphoedema clinched the diagnosis in our case which was confirmed by chromosomal analysis. The infant was discharged and asked to follow up for regular growth monitoring and parents were counselled regarding the condition.